A simple method for predicting alkane‐water partition coefficients of surfactants. Issue 1 (19th August 2021) - Sevastos, Apostolos A.; Baker, Christopher M.; Taylor, Philip
Abstract: Alkane/water (logPalk ) partitioning systems are gaining relevance in applied surfactant science but there is still a challenge to calculate logPalk values for surfactants. In this contribution, a simple method of calculating logPalk at sub‐micellar concentrations for a wide range of nonionic surfactants is presented, using a linear combination of octanol/water partition and hydrogen‐bonding contribution parameters of surfactants. These two parameters can be easily calculated using many commercial or open‐access software packages. The model requires a critical folding chain length factor to account for entropic effects arising from conformational behavior of the ethylene‐oxide chain for alcohol ethoxylate surfactants. This observation is substantiated by conducting a conformational lipophilicity study by molecular dynamics simulations of two alkylphenol ethoxylates as model surfactants. Polydispersity is not seen as a major factor in calculating the logPalk of surfactants. The model is shown to outperform previously published methods and can be applied directly in surfactant research and regulatory submissions when experimental data are not available. Abstract :